LSAC Annual statistical report 2012 - Lodge, Jodie; Baxter, Jennifer (Australian Institute of Family Studies, 2013)
One of the significant ways in which the wellbeing of school-aged children can be eroded is through the effects of being bullied, and as such there is widespread concern over the perceived prevalence of bullying, and the implications this might have for children (Australian Institute of Health and Welfare [AIHW], 2009). This chapter contributes to the current literature on bullying by analysing 10-11 year old children's reports of being picked on through certain unfriendly behaviours that are commonly experienced as bullying behaviours. Specifically, this includes children having been subjected to name-calling, social exclusion, note-writing, and physical violence (i.e., shoving, pushing or hitting). These data were collected from the K cohort of LSAC in 2010 in Wave 4.
Children's experiences of unfriendly behaviour
Keywords: Children; Life Events; Health -- Wellbeing; Child Development; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing; Children; Health; Child Development; Life Events; Wellbeing; Adversity and resilience; Health and wellbeing; Dsiadvantage, adversity and resilience; Childhood and child development